PENGGUNAAN MEDIA PEMBELAJARAN KARTU DOLI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP PADA MATERI LISTRIK - Ali Imron (Universitas Pakuan, 2022)
USE OF DOLI CARD LEARNING MEDIA TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' LEARNING OUTCOMES IN ELECTRICITY LEARNINGThe purpose of the study was to determine the increase in student learning outcomes about electricity in class IX.G through the use of Doli Cards. This research was carried out in a junior high school (SMP Negeri 19 Bogor) in the 2019/2020 school year with the research subjects being class IX.G students. The method used is a classroom action research method which consists of two cycles. In the first cycle the learning was carried out by using Doli Cards in groups without a list of questions, while in the second cycle the use of Doli Cards in groups was accompanied by a list of questions. Each cycle consists of four stages of research, namely planning, implementing actions, observing, and reflecting. The research data were analyzed using comparative descriptive followed by reflection. Comparative descriptive is done by comparing the initial condition data, cycle 1 and cycle 2, both for learning outcomes. The results of this study indicate that: First, the use of Doli Cards can increase students' activities and learning outcomes about electricity in Natural Science subjects in class IX.G. It is proven that the percentage of students in the good learning activity category increased from the initial condition in the first cycle of 62.50% to 84.15 in the second cycle or in the final condition increased by 21.75% from the initial condition. Second, the use of the Doli Card can improve student learning outcomes about electricity in science subjects in class IX.G. It is proven that the percentage of student learning mastery increases from the initial condition of 18.75% to 8556.25 in the first cycle and becomes 93.75% in the second cycle or in the final condition, it increases by 75% from the initial condition.